Fichte's social and political philosophy property and virtue - James, David, 1966-; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2011)
"In this study of Fichte's social and political philosophy, David James offers an interpretation of Fichte's most famous writings in this area, including his Foundations of Natural Right and Addresses to the German Nation, centred on two main themes: property and virtue. These themes provide the basis for a discussion of such issues as what it means to guarantee the freedom of all the citizens of a state, the problem of unequal relations of economic dependence between states, and the differences and connections between the legal and political sphere of right and morality. James also relates Fichte's central social and political ideas to those of other important figures in the history of philosophy, including Locke, Kant and Hegel, as well as to the radical phase of the French Revolution. His account will be of importance to all who are interested in Fichte's philosophy and its intellectual and political context"--
"J. G. Fichte played an essential role in the development of the philosophical movement known as German idealism, appropriating the critical philosophy of Kant in a way that came to influence later thinkers such as Schelling and Hegel. Although there has been a renewed interest in Fichte's philosophy in the English-speaking world, the last book in English by a single author on Fichte's political thought dates back to the 1930s. While I hope to remedy this situation, my discussion of Fichte's social and political philosophy will be limited in two important respects. First of all, this book deals mainly with Fichte's writings in this area belonging to the period from his professorship at the University of Jena to the time of the publication of the Addresses to the German Nation (Reden an die deutsche Nation), a period that extends roughly from 1794 to 1808. Secondly, I limit myself to dealing with two particular themes which I consider to be so integral to Fichte's social and political philosophy that they provide the key to understanding its most basic aims and character. These are the themes of property and virtue, which themselves relate to another concept that is central to Fichte's political philosophy and, indeed, to his philosophy as a whole, namely, freedom"--
Machine generated contents note: 1. Fichte's theory of property; 2. Applying the concept of right: Fichte and Babeuf; 3. Fichte's reappraisal of Kant's theory of cosmopolitan right; 4. The relation of right to morality in Fichte's Jena theory of the state and society; 5. The role of virtue in the Addresses to the German Nation.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Fichte, Johann Gottlieb, -- 1762-1814.; Property -- Philosophy; Virtue; Electronic books